Atmospheric Mercury in Sweden, Northern Finland and Northern Europe. Results from National Monitoring and European Research - Wängberg, Ingvar; Munthe, John (IVL Svenska Miljöinstitutet, 2001)
Atmospheric mercury concentrations and mercury fluxes measured during the period 1995 to 1999 at the AMAP master station of Pallas, a remote station in Northern Finland, and at Rörvik an EMEP station located on the West Coast of Sweden are reported. The result are discussed and compared with atmospheric mercury data generated within the EU-project, Mercury over Europe (MOE). Total particulate mercury exhibit a strong south to north gradient with the highest concentrations in the south, near source areas in Central Europe. Mercury in precipitation also exhibits a south to north gradient Atmospheric mercury concentrations and mercury fluxes measured during the period 1995 to 1999 at the AMAP master station of Pallas, a remote station in Northern Finland, and at Rörvik an EMEP station located on the West Coast of Sweden are reported. The result are discussed and compared with atmospheric mercury data generated within the EU-project, Mercury over Europe (MOE). Total particulate mercury exhibit a strong south to north gradient with the highest concentrations in the south, near source areas in Central Europe. Mercury in precipitation also exhibits a south to north gradient